The Importance of the Educational Department in France for the Education and Treatment of Serbian Youth During the First World War - Žikić, Milena Ž.; Milosavljević, Tanja Č. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The war in the Kingdom of Serbia led to life in exile after 1915. A large population of Serbian youth gathered in France, in addition to parliamentarians, officials, and soldiers. The education of the Serbian youth in France was organized by the Department of Education in Paris. The paper analyses the organization of the Department of Education in France during the First World War. We present the method of education and treatment of students.
Keywords: Department of Education in France; personnel; education of Serbian youth; courses; lyceums; colleges; hospitals